Keratoacanthoma Centrifugum Marginatum with Atypical Scar. (4th December 2012) - Nag, Falguni; Biswas, Projna; Singha, Joydeep; Ghosh, Arghyaprasun; Surana, Trupti V.
Abstract : Keratoacanthoma centrifugum marginatum (KCM) is a rare variant of keratoacanthoma (KA). It is characterized by a progressive peripheral expansion and central healing leaving atrophic scar. It is sometimes confused with squamous cell carcinoma (SCC) both clinically and histopathologically. We here report a case of KCM over the extensor aspect of the right forearm in a 57-year-old man with an abnormal looking scar.